2013
DOI: 10.1080/15389588.2013.808742
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Self-Regulatory Driving Practices Among Older Adults

Abstract: Continuing efforts to better understand the self-regulatory practices of older drivers at multiple levels of driver performance and decision making should provide important insights into how the transition from driving to nondriving can be better managed to balance the interdependent needs of public safety and personal mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 57 publications
1
50
0
Order By: Relevance
“…In the present study too, the older drivers reported driving approximately 60% less than the young drivers. Even though most older people (like other age groups) rely heavily on private vehicles for transportation needs, mileage driven decreases as age increases, trips tend to be shorter, closer to home, and for different purposes than those of younger drivers (Molnar et al, 2014;Rosenbloom, 1999;Whelan et al, 2006). As age increases, urban road use increases and highway use decreases, so that the majority of older drivers do most of their driving in and around their neighborhood (Benekohal, Michaels, Shim, & Resende, 1994).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study too, the older drivers reported driving approximately 60% less than the young drivers. Even though most older people (like other age groups) rely heavily on private vehicles for transportation needs, mileage driven decreases as age increases, trips tend to be shorter, closer to home, and for different purposes than those of younger drivers (Molnar et al, 2014;Rosenbloom, 1999;Whelan et al, 2006). As age increases, urban road use increases and highway use decreases, so that the majority of older drivers do most of their driving in and around their neighborhood (Benekohal, Michaels, Shim, & Resende, 1994).…”
Section: Discussionmentioning
confidence: 97%
“…According to several studies, the travel patterns of older drivers (especially post retirement age) are different than those of young drivers (e.g. Molnar, Charlton, Eby, Langford, & Koppel, 2014;Whelan et al, 2006). In the present study too, the older drivers reported driving approximately 60% less than the young drivers.…”
Section: Discussionmentioning
confidence: 98%
“…For many older people, ageing is accompanied by some decline in their capabilities, cognitive decline and/or physiological complications (Geda et al, 2010;Paterson and Warburton, 2010). These changes coupled with driving cessation (Molnar et al, 2013) and retirement can contribute to social isolation (Liddle et al, 2004) and depression (Marottoli et al, 2000;Ragland et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Digit Symbol Substitution Test (DSST) (Vanlaar et al 2014) Motor Lower extremity strength and dynamic balance Short Physical Performance Battery (SPPB): Side by Side (Guralnik et al 1995;Pahar et al 2014;NHATS 2016) Lower extremity strength and dynamic balance SPPB: Semi-tandem (Guralnik et al 1995;Pahar et al 2014;NHATS 2016) Lower extremity strength and dynamic balance SPPB: Full-tandem (Guralnik et al 1995;Pahar et al 2014;NHATS 2016) Lower extremity strength and dynamic balance SPPB: One Leg Stand Eyes Open (Guralnik et al 1995;Pahar et al 2014;NHATS 2016) Usual gait speed SPPB: Gait Speed Test (Guralnik et al 1995;Pahar et al 2014;NHATS 2016) Lower extremity strength SPPB: Single Chair Stand (Guralnik et al 1995;Pahar et al 2014;NHATS 2016) Lower extremity strength SPPB: Repeated Chair Stand (Guralnik et al 1995 Acuity -dynamic, far, near Tumbling "E" Chart (Marshall et al 2013a;Molnar et al 2014) Contrast sensitivity Pelli Robson Marshall et al 2013a;Molnar et al 2014) Auditory perception Whisper Voice Test Marshall et al 2013a;Molnar et al 2014) Visual spatial skills Motor Visual Perception Test (MVPT) (Marshall et al 2013a;Molnar et al 2014) through pertinent state agencies by the individual study sites. Standard data fields are collected for each crash in which a participant was a driver, regardless of who was at fault.…”
Section: Crash Recordsmentioning
confidence: 99%
“…During the follow-up, crash data are collected annually for the previous year. Crash data are obtained Visuospatial skills Clock Drawing Test Marshall et al 2013aMarshall et al , 2013bMolnar et al 2014) Simple and choice reaction time Deary-Liewald Reaction Time Tester (Deary et al 2011) Episodic/working memory task Immediate and Delayed Word Recall (Wallace and Herzog 1995) Attention, psychomotor speed (perceptual speed, visual scanning, memory)…”
Section: Crash Recordsmentioning
confidence: 99%